Alcohol consumption and its associated factors among pregnant women in Sub-Saharan Africa: a systematic review and meta-analysis' as given in the submission system - Alemu Earsido Addila; Telake Azale Bisetegn; Yigzaw Kebede Gete; Mezgebu Yitayal Mengistu; Getnet Mihretie Beyene (BMC, 2020)
Abstract Background Alcohol consumption during pregnancy represents a significant public health concern. It has several adverse health effects for both the mother and the developing fetus. This study aimed to estimate the pooled prevalence and the effect size of associated factors of alcohol consumption during pregnancy in Sub-Saharan Africa countries. Methods The results of the review were reported based on the Preferred Reporting Items for Systematic Review and Meta-Analysis statement (PRISMA) guideline and, it was registered in the Prospero database, number CRD42019127103. The available primary studies were collated from different databases: PubMed, CINAHL, Cochrane Library, PsycINFO, Google Scholar, African Journals Online and Centre for Addiction and Mental Health Library. The main search terms were [((alcohol consumption) OR (alcohol drinking) OR (alcohol use) OR (ethanol use) OR (alcohol exposure)) AND ((pregnant women) OR (pregnant mother) OR (during pregnancy)) AND (Sub-Saharan Africa)]. We used the Joanna Briggs Institute (JBI) for critical appraisal of studies. The random-effects model was computed to estimate the pooled prevalence. Heterogeneity between studies was checked using the I2 statistic and the Cochrane Q test. Results The review resulted in 963 original studies after searching various databases, and finally 37 studies in qualitative synthesis and 30 articles in the systematic review and meta-analysis were included. The overall summary estimate of the prevalence of alcohol consumption during pregnancy was found to be 20.83% (95% CI: 18.21, 23.46). The pooled estimate of meta-analysis showed that depression (OR: 1.572; 95% CI: 1.34, 1.845), partners' alcohol use (OR: 1.32, 95% CI: 1.11, 1.57), knowledge on harmful effect of alcohol consumption (OR: 0.36, 95% CI: 0.29, 0.45) and, unplanned pregnancy (OR: 2.33, 95% CI: 1.17, 4.63) were statistically significant factors with alcohol consumption during pregnancy. Conclusions The result showed that there was high alcohol consumption during pregnancy in Sub- Saharan Africa. Alcohol consumption during pregnancy was associated with depression, partners' alcohol use, unplanned pregnancy and knowledge of the harmful effects of alcohol consumption. Therefore, this will be a basis for public policy and resource allocation for prevention initiatives.